Pengembangan Sistem Otentikasi Dokumen Digital Jurusan Teknik Informatika Dan Komputer Fakultas Teknik UNM Berbasis Digital Signature - Iin Mahgafhira; Abdul Wahid; Jumadi Mabe Parenreng (Sakura Publisher, 2023)
This study aims to determine the development of a digital document authentication system in the informatics and computer engineering department, Faculty of Engineering, UNM based on digital signatures and the results of testing software quality standards using ISO25010 by implementing 3 aspects, namely functional suitability, performance efficiency and portability. Maintain document authenticity using the MD5 algorithm as a Hash function to produce a message digest and the RSA algorithm as a public key algorithm. This research uses research and development (R&D) with a prototype design model. Testing using ISO25010 by implementing 3 aspects produces a system that is acceptable and feasible to use. As for the results of testing the RSA and MD5 algorithms, it was found that the results of this digital signature-based digital document authentication system can ensure the authenticity and integrity of documents so that they can prevent falsification and manipulation of documents by unauthorized persons.